FBXW7 and the Hallmarks of Cancer: Underlying Mechanisms and Prospective Strategies - Shen, Wenyue; Zhou, Quanwei; Peng, Chenxi; Li, Jiaheng; Yuan, Qizhi; Zhu, Hecheng; Zhao, Ming; Jiang, Xingjun; Liu, Weidong; Ren, Caiping (Frontiers in Oncology, 2022)
FBXW7, a member of F-box protein family within the ubiquitin-proteasome system, performs an indispensable role in orchestrating cellular processes through ubiquitination and degradation of its substrates, such as c-MYC, mTOR, MCL-1, Notch and cyclin E. Mainly functioning as a tumor suppressor, inactivation of FBXW7 induces the aberrations of its downstream pathway, resulting in the occurrence of diseases especially tumorigenesis. Here, we decipher the relationship between FBXW7 and the hallmarks of cancer and discuss the underlying mechanisms. Considering the interplay of cancer hallmarks, we propose several prospective strategies for circumventing the deficits of therapeutic resistance and complete cure of cancer patients.